Control of systemic proteostasis by the nervous system. Issue 1 (January 2015) - Mardones, Pablo; Martínez, Gabriela; Hetz, Claudio
Highlights The proteostasis network mediates cellular adaptation to protein-folding stress. Cell-nonautonomous regulation of peripheral proteostasis is controlled by the central nervous system. Cell-nonautonomous control of proteostasis is implicated in thermoregulation, innate immunity, energy balance, and aging. Targeting the regulation of proteostasis by the nervous system has therapeutic potential.